Field notes contributed by Lee A. Schoenewe, spring 1997 - Schoenewe, Lee A.et al (1997)
List of birds and locations contributed by Lee A. Schoenewe. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of spring 1997. Epson - sheet feed